The industry effects of monetary policy in the euro area - Gert Peersman; Frank Smets (European Central Bank (ECB), 2002)
We first estimate the effects of an euro area-wide monetary policy change on output growth in eleven industries of seven euro area countries over the period 1980-1998. On average the negative effect of an interest rate tightening on output is significantly greater in recessions than in booms. There is, however, considerable cross-industry heterogeneity in both the overall policy effects and the degree of asymmetry across the two business cycle phases. We then explore which industry characteristics can account for this cross-industry heterogeneity. Differences in the overall policy effects can mainly be explained by the durability of the goods produced in the sector. In contrast, differences in the degree of asymmetry of policy effects seem to be related to differences in financial structure, in particular the maturity structure of debt, the coverage ratio, financial leverage and firm size.
Keywords: E4; E5; 330; euro area; financial accelerator; monetary transmission mechanism